Nervous System Injury in Response to Contact With Environmental, Engineered and Planetary Micro- and Nano-Sized Particles - Borisova, Tatiana (Frontiers in Physiology, 2018)
Nerve cells take a special place among other cells in organisms because of their unique function mechanism. The plasma membrane of nerve cells from the one hand performs a classical barrier function, thereby being foremost targeted during contact with micro- and nano-sized particles, and from the other hand it is very intensively involved in nerve signal transmission, i.e. depolarization-induced calcium-dependent compound exocytosis realized via vesicle fusion following by their retrieval and calcium-independent permanent neurotransmitter turnover via plasma membrane neurotransmitter transporters that utilize Na+/K+ electrochemical gradient as a driving force. Worldwide travelling air pollution particulate matter is now considered as a possible trigger factor for the development of a variety of neuropathologies. Micro- and nano-sized particles can reach the central nervous system during inhalation avoiding the blood-brain barrier, thereby making synaptic neurotransmission extremely sensitive to their influence. Neurosafety of environmental, engineered and planetary particles is difficult to predict because they possess other features as compared to bulk materials from which the particles are composed of. The capability of the particles to absorb heavy metals and organic neurotoxic molecules from the environment, and moreover, spontaneously interact with proteins and lipids in organisms and form biomolecular corona can considerably change the particles` features. The absorption capability occasionally makes them worldwide travelling particulate carriers for delivery of environmental neurotoxic compounds to the brain. Discrepancy of the experimental data on neurotoxicity assessment of micro- and nano-sized particles can be associated with a variability of systems, in which neurotoxicity was analyzed and where protein components of the incubation media forming particle biocorona can significantly distort and even eliminate factual particle effects. Specific synaptic mechanisms potentially targeted by environmental, engineered and planetary particles, general principles of particle neurosafety and its failure were discussed. Particle neurotoxic potential depends on their composition, size, shape, surface properties, stability in organisms and environment, capability to absorb neurotoxic compounds, form dust and interrelate with different biomolecules. Changes in these parameters can break primary particle neurosafety.